2018
DOI: 10.1111/birt.12357
|View full text |Cite
|
Sign up to set email alerts
|

Delivery and its complications among women of Somali, Kurdish, and Russian origin, and women in the general population in Finland

Abstract: Delivery complications were more common among migrant Somali women than among women in the general Finnish population. Somali women represent a high-risk group calling for special attention and care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Our findings are broadly comparable to these findings, although we studied emergency and elective caesarean deliveries separately. Our previous study on delivery complications among Somali‐, Russian‐, and Kurdish‐origin migrant women in Finland reported that Russian women were less likely to have a caesarean delivery, which is similar to the findings of this study. We had a smaller and individual country‐specific sample in our previous study, whereas the current study used a larger nationwide data set.…”
Section: Commentsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are broadly comparable to these findings, although we studied emergency and elective caesarean deliveries separately. Our previous study on delivery complications among Somali‐, Russian‐, and Kurdish‐origin migrant women in Finland reported that Russian women were less likely to have a caesarean delivery, which is similar to the findings of this study. We had a smaller and individual country‐specific sample in our previous study, whereas the current study used a larger nationwide data set.…”
Section: Commentsupporting
confidence: 90%
“…The most common risk factors associated with caesarean delivery among migrants are low‐level language skills, lower socio‐economic position, poor maternal health, higher BMI, foetopelvic disproportion, and lack of prenatal care . It has been suggested that the higher risk of elective caesarean deliveries among Latin American/Caribbean‐origin women may also be related to their cultural preferences . Our previous studies on pre‐pregnancy BMI and pregnancy complications (unpublished, under review) among migrant women in Finland showed that Russian women had lower pre‐pregnancy BMI and statistically insignificant lower incidence of pregnancy‐related diabetes and pregnancy‐induced hypertension compared with women in the general population.…”
Section: Commentmentioning
confidence: 98%
See 1 more Smart Citation
“…Acknowledging the cultural aspects may facilitate improvements in reproductive health care and focus on these women's specific needs. Somali women are a highrisk group that demands special attention and care [27].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] However, the results of previous studies have been inconsistent regarding mode of birth, 7,8,10,12,13,15 maternal outcomes 8,10,11 and interventions, 7,15 reflecting heterogeneous study populations, designs and exposure group definitions. Theories regarding better/adverse perinatal outcomes include the healthy migrant effect, 12 socioeconomic disadvantage, 7,8,[10][11][12]16 suboptimal use or access to care, [7][8][9]11,13,16 underlying conditions in the mother 7,10,12,15,16 and the stress of migration. 11,16 Despite increasing global attention to migrants' health, 17 there is limited knowledge on the perinatal health of migrant women in…”
Section: Introductionmentioning
confidence: 99%